Public enemy number two - 9781101176641 (New York Puffin Books, 2014)
Thirteen-year-old Nick Diamond is in prison! Framed for a jewel heist, quick-thinking Nick finds himself sharing a cell with public enemy number one: Johnny Powers. Nick's only chance of clearing his name is to nail the Fence, the country's master criminal. But to do that, he needs to break out'which is where his bumbling older brother, Tim, comes in. Nick's not so sure he'll make it to his fourteenth birthday!